Too Big to Ignore: Lato Sensu Business Students’ Perceptions on an Accounting Big Data Case - Nasu, Vitor Hideo; Nogueira, Daniel Ramos; Albertin, Elvis Araujo; Marques, Claudio (Future Studies Research Journal: Trends and Strategies, 2019)
The objective of this study was to analyze the perceptions of lato sensu business students on an accounting big data case. The case was developed by Hoelscher and Mortimer (2018) and was designed to be used with the Tableau software. It was implemented in two distinct accounting courses from two higher education institutions located in the South region of Brazil. Right after the end of the case’s development, surveys were administered to collect data from the 41 participants. Survey questions were divided into three sections: (i) student’s demographic information; (ii) student’s proficiency level in Excel, Tableau, and Statistical software packages; and (iii) ten case-related and Tableau-related questions that were extracted from prior literature. According to the descriptive statistics, most of the students had low proficiency levels in Tableau before the case’s implementation. After the case, students’ perceptions changed from “none” to “basic” regarding their proficiency level. Also, students found the case interesting, engaging, and useful. It helped them to gain an understanding of how data analytics can be used to answer crucial business questions. Results from the association tests indicated that the students’ demographic and academic information is not significantly associated with the case-related and Tableau-related questions. It means that students who majored in accounting and non-accounting areas had similar perceptions. Then, the case has shown to be a productive activity even for those whose academic background is not directly related to the accounting field. Finally, students’ comments reinforced the positive experience with the case.